2004
DOI: 10.1210/en.2003-1653
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cysteines and Charged Amino Acids in Extracellular Loops of the Human Ca2+Receptor in Cell Surface Expression and Receptor Activation Processes

Abstract: The Ca(2+) receptor is a plasma-membrane bound G protein-coupled receptor stimulated by extracellular calcium [Ca(2+)](o) and other di- and poly-cations. We investigated the role in receptor activation of all the charged amino acid residues and cysteines in the three extracellular loops (EL1, 2, and 3) of the human Ca(2+) receptor by alanine-scanning mutagenesis. The mutant receptors were transiently expressed in HEK-293 cells, and cell surface expression patterns were analyzed by endoglycosidase-H digestion, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…We next examined the ability of OS‐9‐1 to bind to a previously described CaSR mutant (C677A) that remains trapped in the ER due to a predicted misfolding defect (Ray et al, ). Indeed, in Western blots, this mutant reveals only the immature mannose form of the receptor—the mature glycosylated receptor is not produced indicating that it is neither processed by the Golgi nor trafficked to the cell surface (Ray et al, ). We hypothesized that this CaSR mutant might be preferentially targeted by OS‐9.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We next examined the ability of OS‐9‐1 to bind to a previously described CaSR mutant (C677A) that remains trapped in the ER due to a predicted misfolding defect (Ray et al, ). Indeed, in Western blots, this mutant reveals only the immature mannose form of the receptor—the mature glycosylated receptor is not produced indicating that it is neither processed by the Golgi nor trafficked to the cell surface (Ray et al, ). We hypothesized that this CaSR mutant might be preferentially targeted by OS‐9.…”
Section: Resultsmentioning
confidence: 99%
“…The CaSR‐FLAG‐del(895–1075) is expressed in mature form, can reach the cell surface and is functional (Lienhardt et al, ), so it is probable that it has a similar ability to fold as wild‐type receptor. On the other hand, the mutant CaSR‐C677A, ER‐trapped mutant has been predicted to fold improperly (Ray et al, ) suggesting that it would be subject to enhanced trimming of N ‐glycans to favor OS‐9 binding. Surprisingly, however, we did not observe preferential binding of CaSR‐C677A to OS‐9.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It would appear that in the intact hCaR structure the presence of the ECD prevents Calindol from activating the 7TMD. We previously suggested a strong allosteric coupling between the ECD and 7TMD, probably conveyed through interactions with the exo-loops, as a basis for Ca 2ϩ binding in the ECD allosterically activating the 7TMD for G-protein coupling (31 (14). However, we and others (16,21,32) have reported that, whereas Ca 2ϩ alone produces very little or no activation of the ECD-truncated T903-Rhoc construct, in the presence of NPS R-568 and as shown in this study, in the presence of Calindol, Ca 2ϩ dramatically stimulates the 7TMD hCaR construct.…”
Section: Discussionmentioning
confidence: 99%